Potential molecular pathways and therapeutic implications of rapid-acting antidepressants on myelin biology: a scoping review - Inserra, Antonio; Murray, Colin J.; Campanale, Antonella; VanderZwaag, Jared; Tremblay, Marie-Ève (Frontiers in Neuroscience, 2026)
BackgroundEmerging evidence indicates that rapid-acting antidepressants (RAADs)—including ketamine and serotonergic psychedelics- may affect myelin homeostasis, aside from producing fast-onset, sustained improvements in several psychiatric disorders.MethodsA systematic search of PubMed (MEDLINE), Web of Science, Europe PMC, Directory of Open Access Journals (DOAJ), and Google Scholar was conducted up to October 2025 for studies examining the effects of RAADs on myelination and oligodendrocyte biology, as well as associated molecular and cellular mechanisms.Main bodyForty-one studies met the inclusion criteria: 12 in humans, 21 in animals, 7 in vitro, and one computational/theoretical. Thirty studies investigated ketamine and 11 serotonergic RAADs. Across models, RAADs modulate myelination in a dose- and exposure-dependent manner: therapeutic doses generally promote myelin integrity and oligodendrocyte maturation, while high or repeated doses, or neonatal exposure, can disrupt myelin structure and function, impair oligodendrocyte viability, and produce cognitive, affective, and neurotoxic side effects.ConclusionMyelin regulation may represent a component of RAAD action, indicating that these agents could influence myelin biology. Further research is required to clarify the mechanisms underlying these effects, their potential implications for therapies aimed at preserving or restoring myelin integrity, and potential side effects. Their dose-dependent effects highlight the need for careful consideration of dosing and treatment duration.